Role of Bacteria in Tempe Bitter Taste Formation: Microbiological and Molecular Biological Analysis Based on 16S rRNA Gene - TATI BARUS; ANTONIUS SUWANTO; ARIS TRI WAHYUDI; HANNY WIJAYA (Indonesian Society for microbiology, 2008)
Tempe is traditional Indonesian food. It has a variety of tastes, sometimes with a hint of bitterness, which may differ in intensity. The cause of bitterness in tempe has never been reported previously. In this study, the aim is to identify whether bacteria play a role in the formation of bitter tastes in tempe. Sensory tests were carried out in order to determine the scoresof bitter-taste-intensity in tempe. The sensory test on EMP, WJB, CLR, DRG, and MLB tempe shows that EMP tempe has the highest score (2.3) and WJB has the lowest (1.3). It is revealed that the processing method has no impact on the formation of the bitter taste in tempe. Plating analysis, showed that EMP soaking water contained a higher number of Enterobacteria groupbacteria, approximately 103-104 CFU ml-1 and spore-forming bacteria groups, 102 CFU ml-1, compared to WJB. Similarly, other bacteria groups in fresh EMP tempe was 102 CFU g-1 higher than those in fresh WJB tempe. Based on sequencing the16S rRNA gene, the dominant bacteria on PCA media in EMP tempe are Acetobacter indonesiensis, Klebsiella pneumoniae, Bacillus subtilis, and Flavobacterium sp. On the other hand those in WJB tempe were Klebsiella sp., Brevundimonas sp., Bacillus sp., Pseudomonas putida, and Acinetobacter sp. Bacillus, a group of proteolytic bacteria was found 105 CFU m-1 higher in the soaking water of EMP compared to WJB. Nevertheless, the types and numbers of fungi were not significantly different betweentempe types. Accordingly, it is concluded that the difference in the number and the types of bacteria involved in the tempe production process leads to the difference in the bitter taste intensity in both EMP and WJB tempe.